THE DIFFERENTIATED LIPID-LOWERING THERAPY IN WOMEN WITH CORONARY HEART DISEASE IN MENOPAUSE - N. A. Manak; O. A. Barbuk (Евразийский Кардиологический Журнал, 2012)
The aim of the study: to assess the impact of differentiated lipid-lowering therapy on lipid metabolism, immune and inflammatory changes in women with stable angina in menopause. Materials and methods: examined 97 women with stable angina functional class II at menopause (average age 53,6±4,24 years) using instrumental methods (ECG, EKTG-60, Holter ECG monitoring, loading test, coronary angiography) and laboratory (determined by hormonal status, fibrinogen level and hsSRB, lipid profile and blood products LPO). Depending on the identified changes of lipid metabolism prescribed lipid-lowering drugs: atorvastatin, ciprofibrat, combination atorvastatin with antisklerol. Results: after a course of differentiated lipid-lowering therapy in all treatment groups achieved target levels of lipid metabolism. However, in patients receiving atorvastatin significantly decreased the concentration of LPO products (p=0,039) and large molecular 3,5% immune complexes (IC), p=0,041 in early postmenopausal women, of low-molecular 7% IC (p=0,014) in the perimenopause, as well as decreased levels of antibodies to LDL in the late postmenopausal (p